2003
DOI: 10.1074/jbc.m211094200
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor Cell Surface Expression and Cytolytic Pore Formation Are Regulated by a Distal C-terminal Region

Abstract: The importance of the cytosolic C-terminal region of the P2X7 receptor (P2X7R) is unquestioned, yet little is known about the functional domains of this region and how they may contribute to the numerous properties ascribed to this receptor. A structure-function analysis of truncated and single-residue-mutated P2X7 receptors was performed in HEK-293 cells and Xenopus oocytes. Cells expressing receptors truncated at residue 581 (of 595) have negligible ethidium ion uptake, whereas those expressing the P2X7R tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
171
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(183 citation statements)
references
References 30 publications
9
171
0
Order By: Relevance
“…First, P2X 7 receptor mediated NMDG ϩ permeability increases and YOPRO1 uptake have been observed in oocytes that lack native Panx-1 (2,31,32). In contrast, a recent study concluded that these properties could only be measured when Panx-1 was coexpressed (18).…”
Section: Resultsmentioning
confidence: 98%
“…First, P2X 7 receptor mediated NMDG ϩ permeability increases and YOPRO1 uptake have been observed in oocytes that lack native Panx-1 (2,31,32). In contrast, a recent study concluded that these properties could only be measured when Panx-1 was coexpressed (18).…”
Section: Resultsmentioning
confidence: 98%
“…The conserved YXXXK motif found in Cterminal of P2XRs other than P2X7R is necessary for their expression at the cell surface [24]. In human P2X7R, a motif located in the distal region of its C-terminus tail is necessary for proper receptor trafficking; progressive deletions of this tail between residues 551 and 581 are nonfunctional and are not found in the plasma membrane [10,41]. The same motif is also involved in pore dilation [45,48].…”
Section: Discussionmentioning
confidence: 99%
“…The receptor exhibits low sensitivity to ATP, does not desensitize, and gradually develops permeability to organic cations, causing a sustained current growth accompanied by cell blebbing and death [1,12,32,45,50]. The C-terminus of P2X7R is longest among P2XRs and was suggested to account for many of these receptor-specific characteristics [2,41,45]. In contrast, the relevance of the ectodomain structure in P2X7R function has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Only one α-helix is predicted in the TM1 domain, and a major propensity for β-sheet conformation is expected in the TM2 region. The extracellular loop, with 10 conserved cysteine residues forming disulfide bridges and glycosylation sites represents the ATP binding site [22]. The stoichiometry of P2X 7 R involves a trimeric pore that consists of homomultimers [23].…”
Section: P2x 7 Rmentioning
confidence: 99%